Studies On The Floral Biology Of Jackfruit (Artocarpus Heterophyllus Lam.) (Applied Biological Research, 2018)
The experiment was carried out with the aim to study floral biology of  jackfruit using 10 jackfruit genotypes at AICRP on Fruits, BCKV, Mondouri,  West Bengal (India). Floral buds since initiation were continuously observed  for a set of parameters.Bud development in jackfruit took 28-46 days while  successive spike openings took 8–36 days and spikes opening to spathe  shedding 8-16 days. In male spike opening to anthesis ranged from 16 to 32  days and anther sacs availability for 3-7 days. In female spikes, stigmas were  available from 12-34 days and receptive from 5th to 34th days after emergence.  Female spike length ranged from 4.65 to 9.80 cm and diameter from 3.18 to  5.90 cm. Sex ratio was highest in December. Male spike length was 3.8-10.9 cm  and diameter 1.60-3.78 cm. Number of individual flowers spike-1 was 3565- 9831 for female and 2736-1294 for male. The study revealed that genotypes  10/9, 11/6, 11/9 and 11/10 can be used for future crop improvement based on  reproductive traits of male and female parents that ultimately indicates the  quality and yield potential of those individuals.
Keywords: Floral biology; jackfruit; sex ratio; spikes; stigma receptivity